Causal relationship between COVID-19 and myocarditis or pericarditis risk: a bidirectional Mendelian randomization study - Liu, Guihong; Chen, Tao; Zhang, Xin; Hu, Binbin; Shi, Huashan (Frontiers in Cardiovascular Medicine, 2023)
Background & Aims Coronavirus disease 2019 (covid-19) is strongly associated with myocarditis or pericarditis risk in observational studies, however, there are still studies that do not support the above conclusion. Whether the observed association reflects causation needs to be confirmed. We performed a bidirectional Mendelian randomization (MR) study to assess the causal relationship of covid-19, which was divided into three groups, namely severe covid-19, hospitalized covid-19, and covid-19 infection, measured by myocarditis or pericarditis.Methods We extracted summary genome-wide association statistics for the severe covid-19 (case: 13769, control: 1072442), hospitalized covid-19 (case: 32519, control: 2062805), covid-19 infection (case: 122616, control: 2475240), myocarditis(case 1521, control 191924), and pericarditis(case 979, control 286109 ) among individuals of European ancestry. Independent genetic variants that exhibited a significant association with each phenotype at the genome-wide level of significance were utilized as instrumental variables. Estimation of the causal effect was mainly performed using the random effects inverse-variance weighted method (IVW). Additionally, other tests such as MR-Egger intercept, MR-PRESSO, Cochran's Q test, "Leave-one-out", and funnel plots were conducted to assess the extent of pleiotropy and heterogeneity.Results Non-associations in the IVW and sensitivity analyses were observed for covid-19 with myocarditis or pericarditis. Severe covid-19 was not associated with myocarditis [odds ratio (OR), 1.00; 95% confidence interval (CI), 0.89-1.12; P = 0.99], pericarditis (OR = 0.90, 95% CI, 0.78-1.04, P = 0.17). Similar results can be observed in hospitalized covid-19, and covid-19 infection. At the same time, null associations were observed for myocarditis or pericarditis with covid-19 traits in the reverse direction. The main results are kept stable in the sensitivity analysis.There is no evidence that covid-19 is independently and causally associated with myocarditis or pericarditis.